Efficiency Criteria, Income Taxation, and Heterogeneous Elasticities - Becko, John Sturm; Sztutman, André (American Economic Review, 2026)
A common interpretation of Pareto-efficient policies is that, for some cardinal utility representations of preferences, they maximize utilitarian welfare. We show in the context of income taxation that such cardinalizations are often extreme, requiring unbounded curvature of utility with respect to consumption. Taxes can be justified as utilitarian without these extreme cardinalizations if and only if revenues are decreasing and concave in a class of narrowly targeted tax cuts. We reformulate this condition as a sufficient-statistics test. The test fails whenever elasticities of taxable income are too heterogeneous within some income level, as we argue is empirically likely. (JEL D81, H21, H23, H24, J22, J31)